THE INFLUENCE OF GUT MICROBIOTA ON PERFORMANCE IN ATHLETES - Gabriela Barszcz; Natalia Bębenek; Monika Błądek; Karolina Drygała; Sylwia Wit; Paulina Frączkiewicz; Izabela Harpula; Radosław Ramotowski; Justyna Bogdan; Benedykt Baljon; Patryk Brzezicki (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: The gut microbiota, consisting mainly of bacteria, plays a key role in human health, including athletes. Its composition can be modulated by diet, antibiotics, stress, and physical activity. The aim of this paper is to present the influence of the gut microbiota on athletes' performance and to assess the potential benefits of probiotic supplementation.Review methods: The literature search for this review was performed using the PubMed database and other available literature sources and the following keywords: gut microbiota, physical activity, competitive athletes, gut barrier defense mechanisms.A brief description of the state of knowledge: The gut microbiota has protective functions, fermenting undigested carbohydrates, synthesizing vitamins, and metabolizing lipids. Studies suggest that the microbiota can improve metabolic and immune function, which reduces mental fatigue and improves performance in athletes. Probiotic supplementation can increase endurance, aerobic capacity, and recovery from exercise, as well as reduce gastrointestinal symptoms. Probiotics may also affect the mental and cognitive health of athletes through mechanisms related to the gut-brain axis.Conclusions: The gut microbiota plays a significant role in the health and performance of athletes. Probiotic supplementation can provide a variety of benefits, including improved performance, recovery, and mental health. Additionally, it can improve the bioavailability of key nutrients such as branched-chain amino acids (BCAAs), supporting muscle recovery and performance. However, further research is needed to determine the optimal doses and strains of probiotics, as current evidence, although promising, remains limited and not fully validated.